Wave propagation in stratified medium: new matrix form of the wave difference equation - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2018)
Results of research of possibility of transformation of a wave difference equation into a system of the first-order
difference equations are presented. In contrast to the method used previously, an unknown grid function is split into
two new auxiliary functions, which have definite properties. Several examples show that proposed approach can be
used for solving different physical problems associated with the wave propagation in one dimension. Представлені результати дослідження можливості перетворення хвильового різницевого рівняння в систему різницевих рівнянь першого порядку. На відміну від існуючого підходу, в пропонованому методі сіткова функція представляється у вигляді суми двох нових сіткових функцій, які мають певні властивості. Розглянуті приклади показують, що пропонований метод може бути корисним при дослідженні процесів розповсюдження хвиль в одновимірному випадку. Представлены результаты исследования возможности преобразования волнового разностного уравнения
в систему разностных уравнений первого порядка. В отличие от существующего подхода, в предлагаемом
методе сеточная функция представляется в виде суммы двух новых сеточных функций, которые обладают
определенными свойствами. Рассмотренные примеры показывают, что предлагаемый метод может быть
полезным при исследовании процессов распространения волн в одномерном случае.